2022
DOI: 10.1097/mbp.0000000000000625
|View full text |Cite
|
Sign up to set email alerts
|

The association of ambient temperature variability with blood pressure in southern China

Abstract: Objectives Numerous studies have shown a positive relationship between temperature variability and mortality, but few studies have investigated the effect of temperature variability on blood pressure (BP). We aimed to estimate the effect of temperature variability on BP in Guangdong Province, southern China. Methods Data on meteorological factors were obtained from the Guangdong Meteorological Center, and BP was collected from a series of cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The lack of an overall association between TV and hypertension ED visits was surprising. Previous research has found that shorter periods of TV are associated with increased hypertension morbidity (22)(23)(24)(25). One possible explanation is that the physiological effects of TV on hypertension are more immediate than the other outcomes examined in this analysis, making DTR a better exposure of interest for this outcome.…”
Section: Discussionmentioning
confidence: 86%
“…The lack of an overall association between TV and hypertension ED visits was surprising. Previous research has found that shorter periods of TV are associated with increased hypertension morbidity (22)(23)(24)(25). One possible explanation is that the physiological effects of TV on hypertension are more immediate than the other outcomes examined in this analysis, making DTR a better exposure of interest for this outcome.…”
Section: Discussionmentioning
confidence: 86%